Radiofrequency Ablation-Assisted Zero-Ischemia Robotic Laparoscopic Partial Nephrectomy: Oncologic and Functional Outcomes in 49 Patients - Kalen Rimar; Aziz Khambati; Barry B. McGuire; David A. Rebuck; Kent T. Perry; Robert B. Nadler (Advances in Urology)
Introduction and Objectives. Robotic partial nephrectomy with peritumoral radiofrequency ablation (RFA-RPN) is a novel clampless technique. We describe oncologic and functional outcomes in a prospective cohort. Methods. From May, 2007, to December, 2009, 49 consecutive patients with renal masses <7 cm underwent RFA-RPN. During this period, only the RFA-RPN technique was utilized for all cases of partial nephrectomy. Pre- and postoperative data were analyzed and compared to 36 consecutive patients who underwent LPN. Results. In total, 49 tumors were treated in the RFA-RPN group and 36 tumors in the comparison group. Mean operative time was longer in the RFA-RPN group (370 min versus 293 min, p<0.001). There were no significant differences in mean EBL (231 cc versus 250 cc, p=0.42), transfusion rate (8.2% versus 11.1%, p=0.7), or hospital stay (3.9 versus 4.4 days, p=0.2). Two patients in the RFA-RPN (4.1%) and 1 (2.7%) patient in the comparison group had a positive surgical margin (p=0.75). 17 (34.7%) patients had a postoperative urine leak in the RFA-RPN group versus 2 (5.6%) patients in the comparison group (p=0.001). Mean follow-up was 54 months versus 68.4 months in the comparison group. There was no significant difference between the two groups regarding change in GFR (p=0.67). There were 3 recurrences (6.1%) in the RFA-RPN group and 0 recurrences in the RPN group (p=0.23). There were 3 deaths (6.1%) in the RFA-RPN group (one cancer specific) and 4 deaths (11.1%) in the RPN group (non-cancer specific) over the follow-up period (p=0.44). Conclusions. Our data suggests that this technique is associated with a similar degree of renal preservation but higher rates of postoperative urine leak and possibly higher rates of recurrence.